Antimicrobial activity, chemical composition and mechanism of action of Chinese chive (Allium tuberosum Rottler) extracts - Chen, Cun; Cai, Jing; Ren, Ying-hong; Xu, Yue; Liu, Hong-ling; Zhao, Yu-yang; Chen, Xing-fu; Liu, Zhi-bin (Frontiers in Microbiology, 2022)
Chinese chive (Allium tuberosum Rottler) is a popular food from Allium species in East and Southeast Asia. Most Allium species possess characteristic aromas and have antimicrobial activity. In this study, the antimicrobial activities of root, leaf, and scape extracts of Chinese chive at different pH levels (3.0, 5.0, 7.0, 9.0, and 10.7) were compared. The most pronounced activity was produced by the scape extract, and the greatest activity was obtained at pH 5.0. HPLC and GC-MS analysis showed that the major active ingredient was 2-amino-5-methylbenzoic acid. The mechanism of action of Chinese chive scape extracts may involve the depression or disruption of cell membrane integrity, according to our results of the leakage of electrolytes and protein, as well as SEM and TEM observations.